Enzymatic profiling of clinical and environmental isolates of Burkholderia pseudomallei - Liew, S.M.; Tay, S.T.; Wongratanacheewin, S.; Puthucheary, S.D. (Malaysian Society of Parasitology and Tropical Medicine, 2012)
Melioidosis has been recognized as an important cause of sepsis in the tropics. The disease caused by an environmental saprophyte Burkholderia pseudomallei, affects mostly adults with underlying immunocompromised conditions. In this study, the enzymatic profiles of 91 clinical and 9 environmental isolates of B. pseudomallei were evaluated using the APIZYM system, in addition to assessment of protease, phospholipase C and sialidase activities using agar plate methods and other assays. The activity of 10 enzymes - alkaline phosphatase, esterase, esterase lipase, lipase, leucine arylamidase, valine arylamidase, cystine arylamidase, acid phosphatase, naphthol-AS-BI-phosphohydrolase and N-acetyl-β-glucosaminidase were detected in >75% of the clinical isolates. The majority of B. pseudomallei isolates in this study exhibited protease and phospholipase activities. No sialidase activity was detected. Five Burkholderia thailandensis isolates had similar APIZYM profiles as B. pseudomallei clinical isolates except for the lower detection rate for N-acetyl-β-glucosaminidase. The subtle differences in the number of enzymes secreted and the levels of enzymatic activities of phenotypically identical clinical and environmental strains of B. pseudomallei give weight to the fact that the causative agent of melioidodis originates from the environment.